The Influence of Leadership on Employee Morale with Work Motivation as Mediation Effect - Permadi, I Komang Oka; Puspitawati, Ni Made Dwi; Aristana, I Nengah (Jurnal Ecogen, 2024)
The essence of leadership in any organization is to carefully design work structures and systems. Leadership not only guides the company's vision and goals, but also plays an important role in shaping corporate culture, motivating employees, and influencing overall morale. In fact, the phenomenon of research results in the field still shows contradictions and gaps in research results between leadership, work motivation and morale. To overcome these problems, the authors conducted quantitative research using path analysis techniques and SmartPLS software version 4.0.8.8 and used purposive sampling to select samples. The results showed that leadership has a positive effect on work motivation, as well as leadership has a positive effect on morale. Furthermore, work motivation has no effect on work enthusiasm and has no mediating role on leadership with work enthusiasm. Researchers recognize the limitations in this study, which are limited to leadership, work motivation and morale in one company only. For future research, it is recommended to consider adding additional variables or modifying the research model through a moderation approach. In addition, it is recommended to conduct research involving more than one sector to increase the generalizability of the findings.